Prática de gestão de projetos: um estudo de caso da aderência e dissonância da sistemática de uma empresa brasileira de PMBOK - Munk, Rafael (2015)
This thesis aims to evaluate the attractiveness to the small Brazilian investor, from a financial point of view, of a new form of investment, based on characteristics of the Brazilian crowdfunding model and of traditional investment tools, to be called crowdinvesting. Supported by the detailed understanding of the existing crowdfunding model in the country and the identification and mapping of the characteristics of traditional investment instruments, this study seeks to define how the new form of investment would work and examine whether, in comparison with traditional tools, in terms of risk and return, the crowdinvesting model would be competitive in the Brazilian market.